Pengaruh Financial Distress Dan Leverage Terhadap Konservatisme Akuntansi Pada Perusahaan Ritel Yang Terdaftar Di Bursa Efek Indonesia - Saputri, Mira Yulia; Nurtati, Nurtati; Wahyuni EDT, Risa (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2024)
This research aims to see the influence of financial distress and leverage on accounting conservatism. The data source used in this research is secondary data. The type of data used is quantitative data in the form of financial reports that have been uploaded to the Indonesia Stock Exchange (BEI) in 2019-2022. The object of this research is retail companies listed on the Indonesia Stock Exchange in 2019- 2022. So the samples taken using purposive sampling obtained a sample of 14 samples for research. The statistical method used is multiple linear regression analysis, with hypothesis testing using partial tests (t tests) and simultaneous tests (f tests). The results of research hypothesis testing show that financial distress has a negative and significant effect on accounting conservatism, leverage has a positive and significant effect on accounting conservatism, and together the financial distress and leverage variables have an effect on accounting conservatism.